Слоненок пошел учиться: [стихи] / Д. С. Самойлов - Самойлов Давид Самойлович (Эксмо, 2013)
Экземпляры: ф.3 (20131225) / Инвентарный номер: 50230 / Цена: 300.00. / Сис.шифр: Д / Авт.знак: С 17 / ББК: 84(2Рос-Рус)6-4